PENGARUH ACCOUNT COLLECTION PERIOD, INVENTORY COLLECTION PERIOD, AVERAGE PAYMENT PERIOD, DAN CASH CONVERSION CYCLE TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2023 - Prayoga, Azimas; Wijaya, Rico; Jumaili, Salman (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This study aims to determine the effect of Account Collection Period, Inventory Collection Period, Average Payment Period, and Cash Conversion Cycle on Profitability in Industrial Sector Companies Listed on the Indonesia Stock Exchange in 2020-2023. The sampling method uses the purposive sampling method. The sample in this study was 48 companies for 4 years totaling 192 data. Data analysis used Structural Equation Modeling Partial Least Square (SEM-PLS) with WarpPls 8.0 software. The results of this study indicate that Cash Conversion Cycle has a significant effect on profitability. Meanwhile, Account Collection Period, Inventory Collection Period, Average Payment Period partially do not have a significant effect on profitability in Industrial Sector Companies Listed on the Indonesia Stock Exchange in 2020-2023.